A design approach to FDI/FTC of complex networked control systems - Costa, José Sá da (2019)
The design of fault tolerant control (FTC) systems for large-scale complex networked control systems (NCS) is a difficult task due to the large number of sensors and actuators spatially distributed and networked connected. Despite the research effort on developing FTC systems most of these developments are designed globally leading to centralized FTC solutions inadequate to NCS. In this paper we presente the first version of a toolbox based on multi-agent systems to design FTC systems for large-scale complex NCS. This toolbox is based on a decentralized FTC of NCS which relies on casual graph partitioning of the NCS digraph model and on inteligente distributed computing using multi-agents systems.